Morphological and chemical composition of particulate matter in buses exhaust. (2019) - Chernyshev, V.V.; Zakharenko, A.M.; Ugay, S.M.; Hien, T.T.; Hai, L.H.; Olesik, S.M.; Kholodov, A.S.; Zubko, E.; Kokkinakis, M.; Burykina, T.I.; Stratidakis, A.K.; Mezhuev, Ya. O.; et al.
Highlights: Particle size distribution is divided in two groups, particles sized under 50 μm and particles within the range of 100–1000 μm. Soot particles are represented by amorphous carbon, while in 5% of cases structured carbon particles is found. According to RAMAN spectra, large particles are carbon agglomerates of irregular form. Samples contained metals hazardous to organisms such as Al, Cd, Cr, Cu, Fe, Mg, Ni, Pb and Zn. Buses running on diesel fuel are the source of emission of predominantly large particles. Abstract: This research article investigates the particulate matter originated from the exhaust emissions of 20 bus models, within the territory of Vladivostok, Russian Federation. The majority of evaluated buses (17 out of 20) had emissions of large particles with sizes greater than 400 μm, which account for more than 80% of all measured particles. The analysis of the elemental composition showed that the exhaust emissions contained Al, Cd, Cu, Fe, Mg, Ni, Pb, and Zn, with the concentration of Zn prevailing in all samples by two to three orders of magnitude higher than the concentrations of the other elements.